Meta-Analysis of the Influence of the Inquiry Model on Student Learning Outcomes - MIKE, YONIRA; Asrizal, Asrizal (Journal of Innovative Physics Teaching, 2023)
Student success in learning is very necessary to see the extent to which students are able to solve problems. However, it turns out that student learning outcomes are still low. The solution to overcome this problem is to apply the inquiry learning model during learning. This research aims to determine the effect of the inquiry learning model on student learning outcomes. The application of the inquiry model is seen from the level of education and physics and science lessons. This type of research is meta-analysis. Meta-analysis is research carried out by summarizing research data, reviewing and analyzing research data from several previously existing research results. This research article consists of 11 articles that have ISSN. The instruments used are category codes and effect size calculations. The steps of meta-analysis are conducting a literature review, collecting data, researching and assessing articles, analyzing and interpreting articles, and compiling report results. The data analysis technique in this research is to calculate the magnitude of the effect using a formula based on the mean. From the data analysis carried out, two research results can be stated. First, the application of the inquiry learning model has a significant effect on the level of education and subject matter, especially physics and science.